Analisis Cerpen Gang Buntu dalam Antologi Cerpen Sekeping Hati Karya Erisca Febriani dan Firrr Kajian Semiotika dengan Teori Ferdinand de Saussure - Khaerul Fikri; Siti Nurazizah; Heru Prasetyo; Ayu Setiyo Putri (Saka Bahasa: Jurnal Sastra, Bahasa, Pendidikan, dan Budaya, 2025)
This analysis discusses the short story "Gang Buntu" in the book "Sekeping Hati" by Erisca Febriani and Firrrr using Ferdinand de Saussure's semiotic approach. Literary works, especially short stories, are considered as the author's expression to convey experiences and ideas through language. Semiotics, as an analytical tool, helps unravel the signs and symbols in short stories, facilitating a deeper understanding of the author's intended meaning. The short story "Gang Buntu" describes the story of sadness in a settlement, and semiotic analysis reveals various signifiers and signs that contain deep meaning. The research method used is descriptive qualitative, focusing on the technique of reading and understanding short stories and applying Saussure's semiotic theory. The results of the analysis identify signifiers and signs related to the expression of emotions, atmosphere, and changes in time in the story. The meaning implications of these signifiers and signs support the overall understanding of the short story. This study contributes to further understanding of the use of semiotics in analyzing short stories and detailing important elements in literary works   Analisis ini membahas cerpen "Gang Buntu" dalam buku "Sekeping Hati" karya Erisca Febriani dan Firrrr dengan pendekatan semiotika Ferdinand de Saussure. Karya sastra, khususnya cerpen, merupakan ekspresi pengarang untuk menyampaikan pengalaman dan ide melalui bahasa. Semiotika, sebagai alat analisis, membantu mengurai tanda dan simbol dalam cerpen, memberikan pemahaman mendalam terhadap makna yang dimaksudkan oleh pengarang. Cerpen "Gang Buntu" menggambarkan kisah kesedihan, dan analisis semiotika mengungkapkan berbagai penanda dan petanda yang mengandung makna mendalam. Metode penelitian yang digunakan adalah deskriptif kualitatif, dengan fokus pada teknik membaca dan memahami cerpen serta menerapkan teori semiotika Saussure. Hasil analisis mengidentifikasi penanda dan petanda yang berkaitan dengan ekspresi emosi, suasana, dan perubahan waktu dalam cerita. Implikasi makna dari penanda dan petanda ini mendukung pemahaman keseluruhan cerpen. Penelitian ini memberikan kontribusi pada pemahaman lebih lanjut tentang penggunaan semiotika dalam menganalisis cerpen dan merinci elemen-elemen penting dalam karya sastra.